Discovering statistics using IBM SPSS statistics - Field, Andy (Thousand Oaks : Sage Publishing, 2024)
"With its unique combination of humour and step-by-step instruction, this award-winning book is the statistics lifesaver for everyone. From initial theory through to regression, factor analysis and multilevel modelling, Andy Field animates statistics and SPSS software with his famously bizarre examples and activities. Features: Flexible coverage to support students across disciplines and degree programmes Can support classroom or lab learning and assessment Analysis of real data with opportunities to practice statistical skills Highlights common misconceptions and errors A revamped online resource that uses video, case studies, datasets, testbanks and more to help students negotiate project work, master data management techniques, and apply key writing and employability skills Now fully up to date with latest versions of IBM SPSS Statistics©. All the online resources above (video, case studies, datasets, testbanks) can be easily integrated into your institution's virtual learning environment or learning management system. This allows you to customize and curate content for use in module preparation, delivery and assessment"--
2024.
Keywords: SPSS for Windows; Social sciences -- Statistical methods